2010
DOI: 10.1007/s00467-010-1512-3
|View full text |Cite
|
Sign up to set email alerts
|

No juvenile arterial hypertension in sheep multiples despite reduced nephron numbers

Abstract: Low birth weight is associated with an increased risk of metabolic dysfunction and arterial hypertension in later life. Because of their reduced birth weight twins have been used repeatedly as a natural model to investigate prenatal programming of hypertension. To reveal an early impact of lower nephron endowment on blood pressure, we performed a longitudinal study on lambs from single, twin and triplet pregnancies. The lambs were studied from birth until adulthood, including regular blood analyses, measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…In the same way, we have observed that renal function and structure were unaffected in ageing IUGR offspring with a slow postnatal growth [16]. Such a considerable influence of early growth and nutrition on long term blood pressure in rats has been observed in other species, especially in sheep [78, 79]. Finally, adult hypertension and salt sensitive hypertension (52-week-old animals) could be prevented by placing IUGR rat offspring on a low salt diet just 3 weeks after weaning [80].…”
Section: Developmental Origins Of Ckdmentioning
confidence: 64%
“…In the same way, we have observed that renal function and structure were unaffected in ageing IUGR offspring with a slow postnatal growth [16]. Such a considerable influence of early growth and nutrition on long term blood pressure in rats has been observed in other species, especially in sheep [78, 79]. Finally, adult hypertension and salt sensitive hypertension (52-week-old animals) could be prevented by placing IUGR rat offspring on a low salt diet just 3 weeks after weaning [80].…”
Section: Developmental Origins Of Ckdmentioning
confidence: 64%
“…Consistent with this, a recent Swedish study of 16,265 twins found a correlation between LBW and later life hypertension within dizygotic and monozygotic twin pairs, suggesting that individual fetal growth is an important factor, independent of genetic background, impacting developmental programming of adult disease 83. Not all studies confirm the association between birth weight and subsequent blood pressures, however 8486. The relationship appears to be least consistent among US black children but is maintained in African and Caribbean black children, suggesting that genetic and/or environmental factors may be more pivotal in the US population 75,77,78,87…”
Section: Clinical Consequences Of Impaired Developmental Programming mentioning
confidence: 81%
“…These results support findings in our laboratory and in others, and suggest that neonatal nutrition/growth has to be taken into account in the long-term effects of IUGR in this model. The considerable influence of neonatal growth on long-term diseases in rat has been observed in other species, especially in sheep [145,146].…”
Section: Experimental Studiesmentioning
confidence: 98%